Clothes manipulation by robot rippers with roller fingertips - Sahari K.S.M.; Seki H.; Kamiya Y.; Hikizu M. (2023)
Unfolding or spreading is a very important process in clothes handling in order to sort out whether an item is a shirt, skirt, pants, etc. Spreading of clothes basically involves holding two corners of the clothes next to each other. The problem is finding the two corners. Usage of tracing manipulation to find the second corner can solve this problem. However, there are also problems concerning tracing manipulation. One of the major problems is how to retrieve the fabric when it is in danger of slipping away from the gripper. The robot may be able to detect that the fabric is about to slip, but it is hard to retrieve or prevent it. If the robot tries to regrasp the fabric, it would probably slip away. If the robot tries to retrieve the fabric without regrasping it, it would most probably drag the fabric along instead of retrieving it. This is due to the fact that deformable objects are sensitive to contact forces. A simple solution to this problem is to design a special gripper that can trace the edge smoothly and can also perform fabric retrieval. This paper proposes a unique tracing method for towel spreading using two sensors-equipped grippers with a rolling mechanism at the fingertips. Tracing in the context of this paper involves tracing the towel's edge, with the robot movement based on feedback from sensors. The gripper will allow more flexibility towards fabric manipulation. Experimental results have demonstrated the effectiveness of both the method and the grippers. 2010 VSP.